Air Muscle Actuated Low Cost Humanoid Hand - Scarfe, Peter; Lindsay, Euan (ARS, 2006)
The control of humanoid robot hands has historically been expensive due to the cost of precision actuators. This paper presents the design and implementation of a low-cost air muscle actuated humanoid hand developed at Curtin University of Technology. This hand offers 10 individually controllable degrees of freedom ranging from the elbow to the fingers, with overall control handled through a computer GUI. The hand is actuated through 20 McKibben-style air muscles, each supplied by a pneumatic pressure-balancing valve that allows for proportional control to be achieved with simple and inexpensive components. The hand was successfully able to perform a number of human-equivalent tasks, such as grasping and relocating objects.